2018
DOI: 10.5812/jhealthscope.12383
|View full text |Cite
|
Sign up to set email alerts
|

The Iranian Health System Responsiveness after Implementation of Health Transformation Plan: A Study of Jahrom County in Southern Iran

Abstract: Background: Healthcare systems have an intrinsic responsibility to meet medial and non-medical expectations of people. Objectives: The aim of this study was to investigate the Iranian health system responsiveness in the city of Jahrom. Methods: This study comprised of 600 patients from 6 health centers in Jahrom County. Data were gathered via a standard selfreport questionnaire. Logistic regression analysis was used to evaluate data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The service delivery system has been strengthened with the presence of physicians, and health indicators have been improved. It was shown that the urban family physician program increased the accessibility of services (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The service delivery system has been strengthened with the presence of physicians, and health indicators have been improved. It was shown that the urban family physician program increased the accessibility of services (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the essential role of operational planning in organizational performance and the need to convert the sixth economic, social, and cultural five-year development plan into practical plans, in 2015, Iran's Ministry of Health and Medical Education (MoHME) launched the Health Operational Plan (HOP) in the health sector (7). The plan was mandated for all medical universities, blood transfusion organizations, and food and drug organizations throughout the country (4,8). In the aftermath of this effort, a performance monitoring system named Dashboard was established at the macro level of Iran's MoHME and at the levels of vice presidents and organizational heads.…”
Section: Introductionmentioning
confidence: 99%